Phân lập, xác định cấu trúc và tổng hợp một số dẫn xuất của alpha-amyrin từ cây cùm rụm răng - Sung, Trần Văn; Cường, Nguyễn Huy; Ninh, Phạm Thị; Thủy, Trịnh Thị (Vietnam Journal of Chemistry, 2014)
A mixture of three triterpenes was isolated with high yield (0.566%) from the leaves of Ehretia dentata Couch. growing in Hoa Binh province. These compounds could not be separated by CC and preparative TLC. However, on a chemical derivatization we could determine that the main compounds are a-amyrine and its isomer bauerenol. Key words: Ehretia dentata; Boraginaceae; a-amyrine; a-amyrenone; a-amyrenonol; bauerenol.